Development of automated guided vehicle (mechanical system) - Huzairi, Hashim (2009)
Automated Guided Vehicle or AGV is one of material handling equipment that has been widely used in most manufacturing industry today as it provides more flexibility to the systems. The basic concept of the AGV incorporates battery-powered and driverless vehicles with programming capabilities for path selection and positioning. Nowadays, the AGV are equipped to navigate a flexible guide path network that can be easily modified and expanded. This project include the designing and assembling on the base structure for this AGV. Using software SOLIDWORKS 2006, the design of the vehicle can be done with the respect of specification needed. In designing, the weight of the vehicle must be taken into consideration. After the designing, the choices for material must be taken into notice as it may resulting as a dead weight for the vehicle. Next step in this project is, analysis using software to validify the project. The software used for analysis in this project is FEMPRO V22. It is used to find the displacement for this AGV when the load is apply to the base structure and othe components. In this project, the design of this AGV has to be done properly in order the maximum usability of this AGV project. For this project, the mechanical part or system of this AGV will be incorporated with the guidance system done by other students. The choice of the material for the structure is also important as it will compromised the weight to power ratio of this vehicle. The steering system also will be one of the importants of AGV as it will contribute to the radius of turn angle and also the design of the AGV.Through this report, the types of AGV, the basic concept, the classifications of the AGV and the steering mechanism that usually used in common AGV will be reviewed. Then, this report will be focusing on the mechanical design concept of the AGV which combines knowledge on mechanical parts such as the electric motor, gears, wheels, structure of the AGV and others mechanical parts that are essential for this project.